Association of Plasma Soluble Vascular Cell Adhesion Molecule-1 and sCD14 With Mortality in HIV-1–Infected West African Adults With High CD4 Counts. (1st January 2021) - Affi, Roseline; Gabillard, Delphine; Dunyach-Remy, Catherine; Ntakpe, Jean-Baptiste; Moh, Raoul; Badje, Anani; Kouame, Gérard M.; Karcher, Sophie; Le Carrou, Jérome; Danel, Christine; Chevalier, Mathieu F.; Rouzioux, Christine; et al.
Abstract : Background: Several biomarkers of inflammation and coagulation were reported to be associated with HIV disease progression in different settings. In this article, we report the association between 11 biomarkers and medium-term mortality in HIV-infected West African adults. Methods: In Temprano ANRS 12136, antiretroviral therapy (ART)-naive HIV-infected adults with high CD4 counts were randomly assigned either to start ART immediately or defer ART until the World Health Organization criteria were met. Participants who completed the 30-month trial follow-up were invited to participate in a posttrial phase. The posttrial phase end point was all-cause death. We used multivariate Cox proportional models to analyze the association between baseline plasma biomarkers [IL-1ra, IL-6, soluble vascular cell adhesion molecule 1 (sVCAM-1), sCD14, D-dimer, fibrinogen, IP-10, sCD163, albumin, high-sensitivity C-reactive protein, and 16S rDNA] and all-cause death in the Temprano participants randomized to defer ART. Results: Four hundred seventy-seven patients (median age 35 years, 78% women, and median CD4 count: 379 cells/mm 3 ) were randomly assigned to defer starting ART until the World Health Organization criteria were met. The participants were followed for 2646 person-years (median 5.8 years). In the follow-up, 89% of participants started ART and 30 died. In the multivariate analysis adjusted for the study center, sex, baseline CD4 count, isoniazid preventive therapy, plasma HIV-1 RNA, peripheral blood mononuclear cell HIV-1 DNA, and ART, the risk of death was significantly associated with baseline sVCAM-1 (≥1458 vs. <1458: adjusted hazard ratio 2.57, 95% confidence interval: 1.13 to 5.82) and sCD14 (≥2187 vs. <2187: adjusted hazard ratio 2.79, interquartile range 1.29–6.02) levels. Conclusions: In these sub-Saharan African adults with high CD4 counts, pre-ART plasma sVCAM-1 and sCD14 levels were independently associated with mortality. Abstract : Supplemental Digital Content is Available in the Text.